The efficacy of tamsulosin and solifenacin versus tamsulosin alone in double-J stent associated with lower urinary tract symptoms. - Asad Ullah Jan Hafiz; Syed Wajid Ali; Khalid , Sana (International Journal of Endorsing Health Science Research, 2022)
Background: Lithotripsy procedures, especially, Ureterorenoscopy is considered instrumental in treating ureteral stones effectively. In endourological surgery, a pigtail ureteric stent is a widely used method to resolve or prevent ureteral obstruction, promote healing, and reduce the incidence of ureteral strictures. The current study aimed to compare the efficacy of Tamsulosin with Solifenacin and Tamsulosin alone in double-J stents associated with lower urinary tract symptoms using IPS-Score. Methodology: This study was conducted at the Urology Department, Institute of Kidney Diseases (IKD) Peshawar, Pakistan, from Aug 30, 2018, to Feb 28, 2019. Patients with DJ stents were randomly assigned to two groups (Group A & Group B). Group A received Tab Tamsulosin and Solifenacin, while Group B received Tab Tamsulosin alone; the IPS score was calculated at baseline and after 14 days. Results: A total of 100 subjects undergoing unilateral DJ ureteral stenting participated in this study. The post-treatment IPSS Irritative score suggested that Group A has an average IPS score of 4.38+1.77, while in Group B, 6.4+1.55, which was significant with a p-value of 0.000. Conclusion: Post-treatment average IPSS Irritative score of Tamsulosin and Solifenacin combination was less than Tamsulosin alone in patients with unilateral DJ stent.